Self-biased and wide resonance band magnetoelectric effect in series-connected SrFe12O19/Metglas/Pb(Zr, Ti)O3 composites. (7th December 2016) - Ma, J N; Xin, C Z; Ma, J; Lin, Y H; Nan, C W
Abstract: Self-biased and wide resonance band magnetoelectric (ME) response is realized in the series-connected SrFe12 O19 /Metglas/ Pb(Zr, Ti)O3 composites. Both ME composites fabrication and series-connecting method are optimized in this paper. It is found that 2/5—length ratio between SFO ribbon and PZT plate is proposed to maintain the ME resonance property in the ME composites, and that series-connecting the ME components by opposite polarizations with each other is the proposal method to achieve wide resonance band ME response. Without external magnetic field, the self-biased ME composites show a resonance enhanced ME response of over 117 mV Oe −1 in a 30 kHz bandwidth frequency window. Our ME composites present a good potential for application in broadband magnetic field sensors and energy harvesters.